2000
DOI: 10.1002/1521-3773(20001103)39:21<3891::aid-anie3891>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Super-High-Throughput Screening of Enantioselective Catalysts by Using Capillary Array Electrophoresis

Abstract: More than 7000 ee determinations are possible per day in the analysis of (+)/(−)‐cyclohexylethylamine 1. This result demonstrates the potential of capillary array electrophoresis (CAE) with chirally modified electrolytes for the determination of the enantiomeric purity of organic compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
87
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 212 publications
(89 citation statements)
references
References 48 publications
1
87
0
Order By: Relevance
“…This is especially useful as the limited available separation length is often considered to be a limiting factor for an intended MCE separation. Especially for demanding separations like chiral analysis on microchips [7] it has been reported that the separation length has a significant impact on resolution, therefore folded microchannels have been used to enable chiral separations on chips [42,43]. However, the need to incorporate turns, in order to realize long channels on a compact microchip, adds a geometrical contribution to analyte dispersion [44][45][46].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially useful as the limited available separation length is often considered to be a limiting factor for an intended MCE separation. Especially for demanding separations like chiral analysis on microchips [7] it has been reported that the separation length has a significant impact on resolution, therefore folded microchannels have been used to enable chiral separations on chips [42,43]. However, the need to incorporate turns, in order to realize long channels on a compact microchip, adds a geometrical contribution to analyte dispersion [44][45][46].…”
Section: Resultsmentioning
confidence: 99%
“…Microfluidic devices have been applied for electrophoretic separations for a variety of biochemical and chemical analysis [1][2][3][4][5][6][7]. Latest developments in microchip electrophoresis (MCE) have been summarized in recent reviews [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…To date, a number of techniques are under development for the high-throughput enantiomeric composition determination [13][14][15][16][17], including time resolved IR-thermographic method [18][19][20][21], electron spray mass spectrometry [22][23][24][25][26], capillary electrophoresis [27], UV/Vis [28][29][30], circular dichroism [31,32], and fluorescence [33,34]. Among these approaches, optical methods have been attracting increasing attention due to their ability for quick data collection and compatibility with high-throughput screening system.…”
Section: Advances In Chemistrymentioning
confidence: 99%
“…Microfluidic devices have been applied for electrophoretic separations for a variety of biochemical and chemical analysis [1][2][3][4][5][6][7]. Latest developments in microchip electrophoresis (MCE) have been summarized in recent reviews [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%